Optimizing citric acid protocol to control implant-related infections: An in vitro and in situ study - Cordeiro, Jairo M.; Pires, Júlia M.; Souza, João G. S.; Lima, Carolina V.; Bertolini, Martinna M.; Rangel, Elidiane C. [UNESP]; Barão, Valentim A. R. (Wiley, 2021)
Objective: The present study aimed to establish an optimized protocol for biofilm removal from titanium (Ti) surfaces using citric acid (CA) solutions. Background: Biofilm accumulation is the main factor to trigger peri-implant infections and to increase the risk of treatment failures. Although CA has been suggested as the anti-infective agent with highest potential for biofilm removal on Ti, there is no consensus that CA could improve the anti-infective treatment and its effect. Methods: Physical and chemical alterations, electrochemical behavior, cytotoxicity, and antimicrobial effect of CA on Ti discs were evaluated using four concentrations (1, 10, 20, and 40%) and two application methods (immersion and rubbing). Negative control using 0.9% NaCl was used in all experiments. To evaluate whether different application times can have similar response, polymicrobial biofilm (microcosm model) was formed on Ti and treated with CA for 1, 2, 4, and 8 min. An in situ study was conducted to verify whether the established protocol is equally effective in biofilms formed on machined and sandblasted, large-grit, and acid-etched (SLA) Ti surfaces. Results: CA 40% induced significantly higher surface alterations observed by confocal images and profilometry. In general, rubbing protocol decreased the surface roughness and increased the wettability (p < 0.05), exhibiting better surface cleaning by biofilm removal. CA 10% presented no indirect cytotoxicity and, when applied by rubbing for 8 min, presented proper in vitro antibacterial action and potential corrosion inhibition. When CA 10% was rubbed on Ti surfaces for 4 min, it displayed optimum cleaning ability as 8 min, working equally to remove in situ biofilm on machined and SLA surfaces. Conclusions: The application of CA 10% by rubbing for at least 4 min demonstrated to be a promising protocol to eliminate biofilms formed in smooth and rougher surfaces, which could improve implant-related infection therapies.
Keywords: citric acid; decontamination; implants; peri-implantitis